Hydrogen peroxide modulates neuronal excitability and membrane properties in ventral horn neurons of the rat spinal cord. (7th September 2016) - Ohashi, Masayuki; Hirano, Toru; Watanabe, Kei; Shoji, Hirokazu; Ohashi, Nobuko; Baba, Hiroshi; Endo, Naoto; Kohno, Tatsuro
Highlights: This study investigated the effects of H2 O2 on neuronal excitability in rat ventral horn neurons. H2 O2 reduced neuronal excitability via activation of extrasynaptic GABAA receptor (GABAA -R). H2 O2 depressed both medium and slow AHP, indicating that H2 O2 might reduce SK channel conductance. Activation of extrasynaptic GABAA -R or SK channel might attenuate H2 O2 -induced neuronal damage. Abstract: Hydrogen peroxide (H2 O2 ), a reactive oxygen species, is an important signaling molecule for synaptic and neuronal activity in the central nervous system; it is produced excessively in brain ischemia and spinal cord injury. Although H2 O2 -mediated modulations of synaptic transmission have been reported in ventral horn (VH) neurons of the rat spinal cord, the effects of H2 O2 on neuronal excitability and membrane properties remain poorly understood. Accordingly, the present study investigated such effects using a whole-cell patch-clamp technique. The bath-application of H2 O2 decreased neuronal excitability accompanied by decreased input resistance, firing frequency, and action potential amplitude and by increased rheobase. These H2 O2 -mediated changes were induced by activation of extrasynaptic, but not synaptic, GABAA receptors. Indeed, GABAergic tonic currents were enhanced by H2 O2 . On the other hand, the amplitude of medium and slow afterhyperpolarization (mAHP and sAHP), which plays important roles in controlling neuronal excitability and is mediated by small-conductance calcium-activated potassium (SK) channels, was significantly decreased by H2 O2 . When extrasynaptic GABAA receptors were completely blocked, these decreases of mAHP and sAHP persisted, and H2 O2 increased excitability, suggesting that H2 O2 per se might have the potential to increase neuronal excitability via decreased SK channel conductance. These findings indicate that activating extrasynaptic GABAA receptors or SK channels may attenuate acute neuronal damage caused by H2 O2 -induced hyperexcitability and therefore represent a novel therapeutic target for the prevention and treatment of H2 O2 -induced motor neuron disorders.